2019
DOI: 10.1088/1478-3975/ab45bf
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the grammar of transcriptional regulation from RNA polymerase measurements: models and their applications

Abstract: The genomic revolution has indubitably brought about a paradigm shift in the field of molecular biology, wherein we can sequence, write and re-write genomes. In spite of achieving such feats, we still lack a quantitative understanding of how cells integrate environmental and intra-cellular signals at the promoter and accordingly regulate the production of messenger RNAs. This current state of affairs is being redressed by recent experimental breakthroughs which enable the counting of RNA polymerase molecules (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Next, we consider transcription elongation. In vivo (6,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and in vitro (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) experimental studies have reported the asynchronous nature of the motion of RNAP molecules during elongation, which includes ubiquitous pausing and stochastic hopping. To incorporate these features of RNAP elongation in the model, we assume that each individual RNAP molecule on the gene transitions between two states: an active state, in which it stochastically processes (through single basepair (bps) hops) down the gene at a rate k EL , called the hopping rate, or a paused state, in which hopping ceases.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we consider transcription elongation. In vivo (6,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and in vitro (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) experimental studies have reported the asynchronous nature of the motion of RNAP molecules during elongation, which includes ubiquitous pausing and stochastic hopping. To incorporate these features of RNAP elongation in the model, we assume that each individual RNAP molecule on the gene transitions between two states: an active state, in which it stochastically processes (through single basepair (bps) hops) down the gene at a rate k EL , called the hopping rate, or a paused state, in which hopping ceases.…”
Section: Modelmentioning
confidence: 99%
“…In light of the data introduced above, the goal of this article is to develop the theoretical predictions that can be used, in conjunction with single-cell transcribing RNAP distributions, to reveal the molecular mechanisms that control transcription of a given gene. Although previous studies have used mRNA and protein distributions to infer these mechanisms, these measurements are conflated with the stochasticity of downstream processes such as translation, postprocessing, degradation, and partitioning (31)(32)(33)(34)(35)(36)(37)(38)(39). In this work, we use direct measurement of nascent mRNA distributions, which are not subject to these additional sources of variability.…”
Section: Introductionmentioning
confidence: 99%
“…At low expression, noise usually becomes prominent. Nonetheless, a variety of promoters are available with distinct stochastic properties [92].…”
Section: Conclusion-optimization Of Transcriptional Activation and Rmentioning
confidence: 99%
“…At low expression, noise becomes prominent. A variety of promoters are available that can drive expression at a desired level and noise [84].…”
Section: Conclusion: Optimization Of Transcriptional Activation and mentioning
confidence: 99%